PENGARUH SIKAP MAHASISWA MENGENAI SISTEM BANK TERHADAP MINAT MENABUNG DI BANK SYARIAH - Misaeni Misaeni; Y Achdiyat; A Machmud (Pendidikan Ekonomi FPEB Universitas Pendidikan Indonesia, 2020)
This research is motivated by the low interest in saving in Islamic banks in FPEB UPI students. The purpose of this study was to determine the effect of student attitudes regarding the Islamic banking system on interest in saving in Islamic banks. The research method used is an explanatory survey. The population of this study were students of FPEB UPI class of 2013 and 2014 which amounted to 1,122 students. The research sample amounted to 295 students who were taken using the stratified proportional random sampling technique. Data collection techniques through questionnaires, as well as data analysis techniques using simple linear regression. The results show that: (i) respondents have a positive attitude (favorable) to the Islamic banking system with a high level of interest in saving, (ii) students' attitudes about the Islamic banking system have a positive effect on interest in saving in Islamic banks.